Higher Systemic Exposure to Unbound Active Metabolites of Regorafenib Is Associated With Short Progression‐Free Survival in Colorectal Cancer Patients. Issue 3 (10th March 2020) - Kubota, Yutaro; Fujita, Ken‐ichi; Takahashi, Takehiro; Sunakawa, Yu; Ishida, Hiroo; Hamada, Kazuyuki; Ichikawa, Wataru; Tsunoda, Takuya; Shimada, Kazuhiro; Masuo, Yusuke; Kato, Yukio; Sasaki, Yasutsuna
Abstract : Regorafenib treatment improves survival of patients with metastatic colorectal cancer, but it is also characterized by detrimental side effects that may require modified dosing or interval schedules. Regorafenib is metabolized by cytochrome P450 3A4 in the liver to its active metabolites, M‐2 and M‐5. We examined area under the unbound plasma concentration‐time curve (AUCu) to these compounds to establish pharmacokinetic bases for individualized dosing strategies. The plasma protein binding of M‐2 and M‐5 was approximately 10‐fold lower than that of regorafenib, whereas AUCu values for active metabolites on both days 1 and 15 were significantly higher than that of regorafenib. Patients with higher AUCu values of M‐2 or M‐5 on day 1 showed significantly shorter progression‐free survival than others, likely due, at least in part, to treatment discontinuation as a result of adverse events, especially occurred during first cycle.